EXPERIMENTAL STUDY AND ANALYSIS OF SOLAR AIR HEATER USING OF VARIOUS INLET TEMPERATURES - Vishwakarma, Deeksha; Kale, Jyoti (International Journal of Research -GRANTHAALAYAH, 2017)
In this paper, we are make the experimental setup and assembled the various components such as, flats plate glass, wood, collector, inlet port and outlet port. The collector are generated the hot air with the help solar radiation. The collector are aching the air from inlet port and finally hot air are out through outlet port. We are measured the maximum outlet hot air Temperature in °C.